Border fences threaten movements of large mammals in southwestern China post-COVID-19 pandemic - Jue Lei; Lin Wang (Global Ecology and Conservation)
Transboundary areas are known for their rich biodiversity, yet experiencing extensive infrastructure development. During the COVID-19 pandemic, continual border fences were constructed in Yunnan Province and Guangxi Zhuang Autonomous Region (hereafter Yunnan and Guangxi), southwestern China, which may pose huge threats to wildlife movements and weren’t dismantled in the post-pandemic era. To assess the extent of border fences and their impacts on the cross-border movements of mammals, we compiled data from government reports and collected locations through field surveys and visual interpretation of satellite imagery. Our findings indicate that at least 2392 km of border fences were constructed in Yunnan and 517 km in Guangxi, respectively, accounting for 57.74 % and 50.69 % of their national boundaries. Twelve fence points might influence 53 large mammal species within their distribution areas, with most (73 %) experiencing population declines and nearly half (42 %) threatened with extinction. Given the prevalence of border fence construction in this biodiversity hotspot, we advocate for wildlife surveys along border lines, the prompt removal of these temporary fences, and the revegetation of deforested areas. These actions will enhance habitat connectivity and facilitate the cross-border movement of animals, which are crucial for transboundary conservation and aligning with the Kunming-Montreal Global Biodiversity Framework.